2001
DOI: 10.1007/s002530000474
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of sulfanilic acid by Pseudomonas paucimobilis

Abstract: An aerobic bacterium, isolated from a contaminated site, was able to degrade sulfanilic acid (4-aminobenzenesulfonic acid) and was identified as Pseudomonas paucimobilis. The isolate could grow on sulfanilic acid (SA) as its sole carbon and nitrogen source and metabolized the target compound to biomass. The bioconversion capacity depended on the sulfanilic acid concentration; greater than 98% elimination of the hazardous compound was achieved at low (10 mM) sulfanilic acid concentration, and the yield was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 0 publications
2
35
0
3
Order By: Relevance
“…The fact that two strains are involved in the degradation of 4-ABS could indicate that it is not easy to mineralize this compound. However, a single culture of Pseudomonas paucimobilis degraded also 4-ABS (Perei et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that two strains are involved in the degradation of 4-ABS could indicate that it is not easy to mineralize this compound. However, a single culture of Pseudomonas paucimobilis degraded also 4-ABS (Perei et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The aerobic degradation of the related 3-ABS isomer could not be consistently observed during the batch experiments and it was not degraded in the bioreactor experiment. Aerobic degradation of these three isomers by isolated cultures has been described (Thurnheer et al 1986;Feigel & Knackmuss 1988;Perei et al 2001). The degradation of 4-ABS was possible by a co-culture of two stains, Hydrogenophaga palleronii and Agrobacterium radiobacter, that collaborated to mineralize this compound (Feigel & Knackmuss 1988, 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Because ABS has high polar structure with sulfonic acid group, this may be the reason why ABS is recalcitrant for biodegradation. Some single strains were reported to degrade ABS (Junker et al, 1994;Perei et al, 2001;Singh et al, 2006;Wang et al, 2009). Degradation of ABS by a mixed culture indicated that mutual interactions induced the degradation of ABS (Fiegel et al, 1993).…”
Section: Degradation Kinetics Of Abs By Abs-degrading Consortiummentioning
confidence: 99%
“…The high chemical oxygen demand (COD) characteristics of the chemical synthesis-based pharmaceutical wastewaters make them potential candidates for anaerobic treatment. However, it is well known that many chemicals, especially aromatic pollutants originated from chemical synthesis such as sulfanilic acid and its derivatives are hardly anaerobically degraded [1]. In particular, some of these compounds may be inhibitory to activities of wastewater treatment microbes.…”
Section: Introductionmentioning
confidence: 99%